Certain Formulas for Jacobi Polynomials of Several Variables - Ahmed Ali Atash; Salem Saleh Barahmah (International Journal of Mathematics And its Applications, 2015)
The aim of this research paper is to derive some generating functions of Jacobi polynomials of several variables [4]. Many applications of our main results lead us to obtain some hypergeometric formulas of Jacobi polynomials of two, three and several variables.Some generating functions (known or new) of Jacobi polynomials have been obtained as special cases of our main results.